Z badań nad krzemieniarstwem kultury lendzielskiej na Kujawach: (Ze studiów nad rozwojem kultur wstęgowych na Kujawach) - Domańska, Lucyna (Acta Universitatis Lodziensis. Folia Archaeologica, 1982)
The paper contains ananalysis of flint materials belonging to the Lengyel culture in the region of Kujawy. The analysis included materials coming from the following excavations: Krusza Zamkowa (administrative district of Inowrocław), Konary (adm. district of Dąbrowa Biskupia ), Kościelec (adm. district of Pakość) excavated by the Kujawy Expedition of Institute of Archeology University of Adam Mickiewicz in Poznań, headed by doc. dr habil. A. Cofta-Broniewska as well as materials from archeological locations groupe in the Pakoskie Lake gully (Broniewice, adm. district of Mogilno, Dobieszewice, adm. district of Mogilno, Jankowo, adm. district of Pakość) discovered in the course of salvage researches conducted by Archeological and Conservation Laboratory PKZ in Poznań. The analyzed materials represent two developmental horizons in the Lengyel culture in the Kujawy region: the Early-Lengyeland the Late-Lengyel horizons. This chronological differentiation is also reflected in differentiation of technological-utility rules between both horizons. Technological difference concerns mainly rules of obtaining semi-raw materials. In materials belonging to the Early-Lengyel horizon (Jankowo 4, 15, Konary 20) there appeared flakes and blades cores with one striking surface while in findings of the Late-Lengyel culture dominate technique, which is bipolar flaking on an anavil. Toxonomic differences in the set of tools concern mainly the group of scrapers, which appeared to be quite numerous in the collection coming from the Early-Lengyel horizon with almost complete dificit of them in the Late-Lengyel collection, in the latter-retouch and microretouch specimens obtain a high index. The presented differences between materials provided by the Early-Lengyel horizon (Konary 20) and Late-Lengyel horizon (Broniewice 1/18) find their confirmation in development of the "lowland" group of the Lengyel culture. Flint materials of the Early-Lengyel horizon in Kujawy show many features common with excavations of the so-called Malicka group, and with excavations included by J. K. Kozłowski to the first chronological horizon in the Lengyel culture.